Phantom Study of the Optimum Irradiation Angle for Proton Beam Therapy in Hepatocellular Carcinoma - Tochinai, T.; Someya, T.; Rachi, T.; Akita, T. (International journal of radiation oncology, biology, physics, 2022)
Passive proton beam therapy (PPBT) for hepatocellular carcinoma (HCC) has a higher local control rate than surgery or photon beam therapy. Moreover, it is attracting attention as one of the new treatment options. In the PPBT planning, the selection of the beam angle is determined according to the subjective judgment of the planner. Therefore, there are differences in the dose distribution depending on the planner. It has not yet been clarified which the irradiation angle can be selected to reduce unnecessary dose on the organ-at-risks and maintain the target coverage. The purpose of this study was to determining the optimal beam angle for liver S8 lesions. The subjects were fifty-four treatment plans for HCC located in S8 irradiated using PPBT during the period of 2012.6-2021.3 at the National Cancer Center Hospital East. Tumor sizes were aggregated from the subjects. Clinical Target Volume (CTV) of the subject's liver ranged from 4 cm3 to 1370 cm3. Tumor sizes ranged from 132 cm to 655 cm3. From these results, the average CTV were represented on a virtual phantom, the dose distribution using PPBT was optimized using two irradiation angles. For the calculation of the optimum irradiation angle, the combination of the two beams rotated every 10 degrees and the best dose distribution was considered to be the optimum angle. The Conformity Index (CI) and Homogeneity Index (HI) of the CTV and the V30 (%) of the liver were calculated using the Dose volume histogram (DVH). The combination of beam angles showing 1 in the Conformity Index was 360 ° and 250 °, 350 ° and 230 °, 260 ° and 190 ° for small tumor volumes. Homogeneity Index and V30 averaged 1.06 and 28.0%, respectively. At the time of large tumor volume, it was 350 ° and 270 °, 350 ° and 250 °, 250 ° and 170 °. Homogeneity Index and V30 averaged 1.07 and 47.6%, respectively. The treatment schemes beam-arranged with a 70 ° difference in angle between the two beams were the most homogeneous with respect to the target. A significant difference was found in Conformity Index when compared to the most heterogeneous 190 ° difference (p <0.05). Based on our findings, we recommend using a 2-beam configuration with a beam tilted by approximately 70 ° between the two beams for passive irradiation of hepatocellular carcinoma located in S8. This has the potential to achieve a uniform dose distribution within the target and at the same time reduce the hepatic dose. However, it should be noted that there is a difference in dose increase / decrease depending on the positional relationship of organs and tumors. Further treatment planning studies on aspects of respiration and organ movement need to be conducted.